2010
DOI: 10.1007/s00381-010-1326-4
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal extension of heterotopic glioneuronal tissue: pathoanatomic considerations in symptomatic neonates

Abstract: Transsphenoidal glioneuronal heterotopia should be the top differential diagnosis in MR imaging if a non-enhancing nasopharyngeal mass of an infant extends through a craniopharyngeal cleft within the intersphenoid synchondrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…The bony defect was covered with a mucosal flap during the surgery performed on the ninth day of life, and postoperative meningitis was not seen. Kau et al reported two cases of neuroglial heterotopia in the nasopharynx presenting as transsphenoidal extension of hypothalamic hamartoma through the sphenoid bone 10. Although the intracranial mass lesion was not demonstrated in our case, the neuroradiological features of the connection in this case were quite similar to those of the cases reported by Kau et al 10.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The bony defect was covered with a mucosal flap during the surgery performed on the ninth day of life, and postoperative meningitis was not seen. Kau et al reported two cases of neuroglial heterotopia in the nasopharynx presenting as transsphenoidal extension of hypothalamic hamartoma through the sphenoid bone 10. Although the intracranial mass lesion was not demonstrated in our case, the neuroradiological features of the connection in this case were quite similar to those of the cases reported by Kau et al 10.…”
Section: Discussionsupporting
confidence: 83%
“…Kau et al reported two cases of neuroglial heterotopia in the nasopharynx presenting as transsphenoidal extension of hypothalamic hamartoma through the sphenoid bone 10. Although the intracranial mass lesion was not demonstrated in our case, the neuroradiological features of the connection in this case were quite similar to those of the cases reported by Kau et al 10. Intracranial origin of the connection was in the right optic nerve, which was adjacent to the hypothalamic area.…”
Section: Discussionsupporting
confidence: 81%